Pembentukan Lembaga Kerja Sama Bipartit Pasca Berlakunya Penetapan Peraturan Presiden Pengganti Undang-Undang Cipta Kerja Menjadi Undang-Undang - Azriyal, Raul Maulid; Pratama, Rio Arif; Surahman, Surahman (Bacarita Law Journal, 2025)
The passage of the Presidential Regulation in Lieu of the Law on Job Creation as outlined in Law Number 6 of 2023, the Bipartite Cooperation Institution was formed. This paper examines the legal elements behind the establishment of the Bipartite Cooperation Institute. The Bipartite Cooperation Institute functions as a forum for communication between employers and workers in an organization with the aim of fostering positive working relationships, but there are obstacles in the implementation of Article 190 of the Manpower Law because there are no technical provisions regarding administrative sanctions for business actors who are not members of the Bipartite Cooperation Institution. Primary and secondary legal sources are analyzed using normative legal techniques. The results of the study show that changes in regulations in the Job Creation Law cause legal uncertainty related to the establishment and implementation of Bipartite Cooperation Institutions. Although the establishment of a Bipartite Cooperation Institute is mandatory for companies with more than 50 workers, the administrative sanctions regulated have not been effectively implemented. As a result, many companies do not comply with these obligations, thus hindering efforts to create productive and conducive industrial relations. This study recommends the need for clear technical arrangements regarding sanctions enforcement mechanisms, more massive socialization, and increased active participation of employers and workers, so that the Bipartite Cooperation Institution can function optimally in preventing industrial conflicts and supporting sustainable employment development.